Examining the Effects of Expressive Arts Therapy on Emotional Regulation and Self-Compassion in Adolescent Populations - Pandey, Prashant (Journal of Research in Vocational Education, 2026)
Adolescent mental health is a critical global concern, given the unique challenges faced by this age group. Creating safe and non-judgmental spaces in educational settings is essential for promoting wellbeing and emotional expression. This study aimed to assess the impact of Expressive Art Therapy (EXA) on enhancing emotional regulation and self-compassion, and to determine the causes of lower self-compassion and poorer emotional regulation among adolescents. A quasi-experimental single-group pre-test-post-test mixed- method design was employed, 8 EXA sessions were offered over 8weeks. Participants included 108 adolescents aged 13 to 15 from two mainstream schools in Western Maharashtra, selected via convenient sampling. Quantitative data was collected using the Emotional Regulation Scale (ERQ) and Self-Compassion Scale (SCS), with statistical analysis conducted using IBM SPSS Statistics Version 25. Qualitative data was gathered through expressive movement, artwork, skits, and interviews. Results indicated Significant increase in common humanity subscale scores for both boys and girls (P=0.002). Girls exhibited higher self-compassion scores than boys (P=0.04*), though self-judgment subscale scores increased more in girls (P=0.04*). Moderately positive correlation between self-compassion and emotional regulation scores among boys (P=0.004) was observed resulting in Pearson correlation coefficient of 0.380**. Qualitative analysis showed a 25% improvement in emotional control among 11 students and a 25% improvement in self-compassion among 22 students. The study highlights the benefits of EXA in addressing nonverbal communication related to attachment styles, stress, and anxiety. However, the lack of a control group, limited number of sessions, and small sample size limit the generalizability of the findings. Integrating successful EXA interventions into community centres and educational institutions could provide a supportive framework for adolescents.